Delineation of groundwater potential zone using remote sensing and GIS-based AHP for sustainable groundwater management in Aceh Besar Regency, Aceh Province, Indonesia - Razi, Muhammad Haikal; Zahratunnisa, Zahratunnisa; Retongga, Nofrohu (Brawijaya University, 2024)
Sustainable groundwater management is crucial for ensuring the long-term availability of water resources and supporting socio-economic activities. As water demands increase and hydrological systems become more complex, accurately identifying groundwater potential zones is essential for effective resource planning and utilization. However, the in-situ data availability is often very limited, particularly on a regional scale. To solve this problem, this study aimed to delineate groundwater potential zones in Aceh Besar Regency using remote sensing and a GIS-based AHP (analytical hierarchy process). Several factors were used to determine groundwater potential zones, including lithology, land use/land cover, slope, lineament density, drainage density, rainfall, and soil type. Each factor was weighted based on an extensive literature review and knowledge-driven decision-making techniques. The results indicated that 26.35% of the area was classified as having low groundwater potential, whereas 53.86% was classified as moderate. Areas that have high to very high groundwater potential cover 16.76% to 3.04% of the Aceh Besar territory. The high groundwater potential zones were mostly located in alluvial and clastic sediments lithology, gentle slopes, and had high annual rainfall. Meanwhile, areas with igneous and metamorphic lithology as well as steep slopes, had moderate to low groundwater potential. Validation was carried out by collecting the high-yield existing production wells and calculating the area under the curve (AUC) of the receiver operating characteristic (ROC) curve with relatively good accuracy (74.5%). This research has effectively described the spatial distribution of groundwater potential, contributing to sustainable groundwater management and enabling informed decision-making for sustainable groundwater practices.